2014
DOI: 10.1137/120902252
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Observer Design for Lur'e Systems with Multivalued, Nonmonotone, Time-Varying Nonlinearities and State Jumps

Abstract: International audienceThis paper deals with the stability and observer design for Lur'e systems with multivalued nonlinearities, which are not necessarily monotone or time-invariant. Such differential inclusions model the motion of state trajectories which are constrained to evolve inside time-varying nonconvex sets. Using Lyapunov-based analysis, sufficient conditions are proposed for local stability in such systems, while specifying the basin of attraction. If the sets governing the motion of state trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
2
43
0
1
Order By: Relevance
“…3 and is also used in deriving conditions for stability of the system, which is the main topic of this paper. Certain analysis techniques developed in this paper have been inspired from our recent work on stability of multivalued nonsmooth systems [42], where we also use measure-theoretic notions for modeling state trajectories subjected to nonconvex constraints. The two notions of stability for MDEs considered in this article are:…”
Section: Contributionmentioning
confidence: 99%
“…3 and is also used in deriving conditions for stability of the system, which is the main topic of this paper. Certain analysis techniques developed in this paper have been inspired from our recent work on stability of multivalued nonsmooth systems [42], where we also use measure-theoretic notions for modeling state trajectories subjected to nonconvex constraints. The two notions of stability for MDEs considered in this article are:…”
Section: Contributionmentioning
confidence: 99%
“…For brevity, we have suppressed the time argument in (22), and will do so in the remainder of this section unless required. Let us also introduce the following notation:…”
Section: Error Feedback and Dynamic Compensatormentioning
confidence: 99%
“…In this regard, we mention the recent work on observer design of switched systems with ordinary differential equations [34], [38], [39], switched differential-algebraic equations [40], [41], certain classes of differential inclusions [10], [29], [36], complementarity systems [17], and the references therein for more details. Classical approaches for observer design are based on constructing an auxiliary dynamical system driven by the error between the measured output and the estimated output, where it is shown that the resulting dynamics of the state estimation error converge to the origin.…”
Section: Introductionmentioning
confidence: 99%